Marketing Public Relations Strategy Through Buy 1 Get 1 Promotion at Maxx Coffee - Abdul Kholik; Menati Fajar Rizki (Journal of Research in Social Science and Humanities, 2024)
This study employs a qualitative methodology with a descriptive qualitative approach. Data collection techniques include in-depth interviews, observation, and documentation. The key informants interviewed in this study are the Local Store Marketing Promotion Officer of PT. Maxx Coffee Prima, and two other informants, namely the Area Manager of Maxx Coffee and the Store Manager at Maxx Coffee Pejaten Village.  The three methods used for the Buy 1 Get 1 promotion greatly support the success of Maxx Coffee's marketing public relations, especially through the use of social media, considering that social media currently has a wide reach and is very effective for disseminating information. Based on the results of this study, the researcher concludes that there is a visible positive impact from the implementation of the marketing public relations strategy through the Buy 1 Get 1 promotion by Maxx Coffee through several methods, including online and offline strategies, promotional events, and publications. These three methods of the Buy 1 Get 1 promotion can significantly influence the sales of Maxx Coffee products